An assessment of household food security status and food security determinants in Brazzaville informal settlement, Pretoria - Mkhatshane, Nhlamulo William (My University, 2019)
South Africa’s population is more than 60% urbanised. Although food poverty has historically been associated with rural communities, this is no longer the case. With sustained urbanisation, food insecurity is now being experienced in the urban areas as well. The aim of this study was therefore to assess household food security levels and determinants, and to examine household food security coping strategies in Brazzaville informal settlement, Pretoria. The study adopted a quantitative approach which involved the collection of information through a standardised household questionnaire. A statistically representative sample of 95 households participated in the study. Household questionnaires were used to collect information on household demographics, income and expenditure statistics, poverty data as well as household food access issues. In terms of data analysis, the survey used three measures of household food insecurity: a) the Household Food Insecurity Access Prevalence Indicator (HFIAP); b) the Household Dietary Diversity Score (HDDS); and c) the Months of Adequate Household Food Provisioning (MAHFP) measurements of household food access. The survey results indicate that 29.5% of households in Brazzaville informal settlement were food secure and 70.5% food insecure. Contrary to conventional wisdom of female-headed households being the most food insecure, results of this study show that maleheaded households were the most food insecure. In addition, households with low incomes, low level of education, and high unemployment were also likely to be food insecure. The results of the regression analysis suggest that gender, household income, and employment influences household food security. The probability of food security decreases if household is headed by a female, because females can adopt multiple coping strategies. The study concludes that food insecurity coping strategies vary significantly from one household to another according to their expenses, objectives and constrains. Keywords: Household food insecurity, urbanisation, livelihood, Brazzaville informal settlement, coping strategies.
Thesis (M.Sc. (Geography)) -- University of Limpopo, 2019
Keywords: Household food insecurity; Urbanisation; Livelihood; Brazzaville informal settlement; Coping strategies; Food security; Food supply; Squarter settlements